2016
DOI: 10.1039/c6dt01350c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of reactivity and structure formation in a K–Te–U oxo-system under high-temperature/high-pressure conditions

Abstract: The high-temperature/high-pressure treatment of the K-Te-U oxo-family at 1100 °C and 3.5 GPa results in the crystallization of a series of novel uranyl tellurium compounds, K[(UO)(TeO)], K[(UO)TeO], α-K[(UO)TeO] and β-K[(UO)TeO]. In contrast to most of the reported uranyl compounds which are favorable in layered structures, we found that under extreme conditions, the potassium uranyl oxo-tellurium compounds preferably crystallized in three-dimensional (3D) framework structures with complex topologies. Anion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…29 For the U− As Recently, we found that high-temperature/highpressure conditions increase the diversity of U−Se/Te 4+ −O frameworks due to the variation of coordination geometries of Te 4+ and U 6+ . 33,34 The average CN of U for U−Se/Te 4+ −O family (5.04) is close to that for U−P/As 3+ −O, which is attributed to the same ionic potential (0.06) for both systems. By analyzing the coordination environments of uranyl ions in all known U 6+ −T−O phases, we found that the ionic potential of central cations T in oxo-anion groups in their higher oxidation states correlates to the CNs of uranyl ions in these materials.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…29 For the U− As Recently, we found that high-temperature/highpressure conditions increase the diversity of U−Se/Te 4+ −O frameworks due to the variation of coordination geometries of Te 4+ and U 6+ . 33,34 The average CN of U for U−Se/Te 4+ −O family (5.04) is close to that for U−P/As 3+ −O, which is attributed to the same ionic potential (0.06) for both systems. By analyzing the coordination environments of uranyl ions in all known U 6+ −T−O phases, we found that the ionic potential of central cations T in oxo-anion groups in their higher oxidation states correlates to the CNs of uranyl ions in these materials.…”
Section: Resultsmentioning
confidence: 63%
“…Almost half of the structures for the U–Se/Te 4+ –O system have 5-coordinated uranyl, and structures of 10 phases possess mixed 4- and 5-coordinated and 5- and 6-coordinated uranyls. Recently, we found that high-temperature/high-pressure conditions increase the diversity of U–Se/Te 4+ –O frameworks due to the variation of coordination geometries of Te 4+ and U 6+ . , The average CN of U for U–Se/Te 4+ –O family (5.04) is close to that for U–P/As 3+ –O, which is attributed to the same ionic potential (0.06) for both systems.…”
Section: Resultsmentioning
confidence: 81%
“…30 Under the extreme condition, the compounds tend to crystallize in unconventional structure types which are dramatically different from those synthesized via conventional high-temperature or hydrothermal conditions, as demonstrated in the high probability of noncentrosymmetric observed in the Na-U-Te oxo-system and the structural complexity of the K-U-Te group. 31 However, compared to the tremendous success achieved from the uranium oxo-tellurium family, very few details are known about the formation and crystal structures of thorium counterparts. The only representative in the thorium oxotellurium family with a refined crystal structure is ThTe 2 O 6 , which was obtained more than 30 years ago from a solid-state method at a temperature of 700 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of findings in this field are the reports of rich noncentrosymmetry in the Na−U−Te oxo-system 16 or increased atypical structure types with more complex structures and dimensionalities in the K− U−Te or K−U−Mo oxo-systems. 17 . 18 The title phase, Na 4 [(UO 2 )(SO 4 ) 3 ], was obtained under an extreme conditions study of the A I −U−S system (A I -alkali metals).…”
mentioning
confidence: 99%
“…Our focus of the study was on investigating the phase formation behavior of actinide oxo-chalcogenates under high-temperature/high-pressure conditions. Examples of findings in this field are the reports of rich noncentrosymmetry in the Na–U–Te oxo-system or increased atypical structure types with more complex structures and dimensionalities in the K–U–Te or K–U–Mo oxo-systems .…”
mentioning
confidence: 99%